Two new marine species from South Korea with remarks on the family Stylochidae (Acotylea, Polycladida, Plathelminthes) - Bulnes, Verónica Natalia (2005)
Two new species of acotylean Polycladida are described from Korea, Munseoma maculata gen. et sp. nov., Callioplanidae, and Crytostylochus koreensis sp. nov., Stylochidae. Munseoma maculata is characterized by a small free prostatic vesicle but only indistinctly cut off from the ejaculatory duct; a Lang's vesicle is present. Crytostylochus koreensis possesses a prostatic vesicle with tubular lining of radial arrangement. Each papillate tube is connected via a glandular duct to a single extra-vesicular gland attached to the muscular wall of the prostatic vesicle. That morphological feature forces discussion of the relationships within the family Stylochidae. Consequently, type material of other stylochids deposited in the museums of Hamburg, Vienna, and Stockholm was borrowed to investigate the genital organs and, in particular, the interior lining of the prostatic vesicle. Based on these analyses, two new types of prostatic lining are defined, the polyglandular type and the monoglandular type. The monoglandular type is defined as having an oval to elongate prostatic vesicle with tubular lining and extra-vesicular glands. Each extra-vesicular gland is connected via a glandular duct with a single tube. The polyglandular type is defined as having a mostly roundish oval prostatic vesicle with long-fingered extensions, more or less horizontally directed distad, and numerous extra-vesicular glands. Each long-fingered extension is connected via several glandular ducts of extra-vesicular glands. Based on these new characters, the family Stylochidae is newly defined.